(untitled) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2015)
The coastal area of the East Coast County of Banyuasin has high potential to be developed, but this region is a region that is experiencing a high process of sedimentation, as a result is the superficiality which can affect the movement of the water. The activities that occur in the coastal waters comes either from the land as agriculture, forestry, animal husbandry, industry, settlement and development of the ports as well as others or activities originating from the waters like the waves, current, tides, etc. Activities that occur in both land and water influenced the coastal areas of Banyuasin. This research aims to look at the distribution of sedimentation, gradients , identify the rate of sedimentation dan sedimentation forming parameters in coastal waters Banyuasin II. For the location of the research that distribution of sandying mud sedimentation, grading tersorting good or uniform, fine-grained skew taper-shaped curve, the feet support the formation of sedimentation and is rate of sedimentation is 0,00953 km/m2/day and that is experiencing high sedimentation is Tanjung Sere while that is experiencing the lowest rate of sedimentation was Tanjung Api-Api about 0,00120 km/m2/day. Keywords : Identification , Sedimentation, Coastal waters